Authentic Assessment Management Strategies for Enhancing Student Creativity in Islamic Education: A Systematic Literature Review - M. Yusuf Aminuddin (Fakultas Agama Islam Universitas Billfath, 2026)
through a Systematic Literature Review (SLR) approach. The literature search was conducted using Harzing Publish or Perish (PoP) from the Scopus, Google Scholar, Semantic Scholar, and Crossref databases, and supported by Elicit as an additional source. The literature selection process followed PRISMA 2020 with inclusion criteria: journal articles indexed by SINTA and Scopus published in the 2020-2025 period, and relevant to the research topic. Of the 1,212 identified articles, 8 articles met the criteria and were analyzed in depth. The results of the study indicate that authentic assessment contributes to the development of student creativity through the integration of cognitive, affective, and psychomotor aspects, the application of contextual tasks, and the provision of constructive feedback in the learning process. In its implementation, it still faces obstacles, especially in classes with large numbers, so that the assessment of attitudes and skills aspects is not optimal. Strengthening the management of authentic assessment systematically and consistently is needed to support more meaningful learning.